O ensino religioso e sua contribuição para o desenvolvimento ético do aluno na perspectiva dos parâmentros curriculares nacionais - Vasconcelos, José Roberto de (2012)
The education has the character of fonning the citizen for the life, being in syntony with the reality that surrounds the student. The Religious Teaching (RT) has the indicative ofworking the Religious Phenomenon in an including way. The concern of fonning the student with the critical conscience and a vision of including world, also goes by the understanding, as well as the systematic study of the religion, while institution that has its presence in the history, working the human being while looking for the transcendence. Before a world marked by conflicts and in a society gane back to the consumerism, something very pertinent in the Post- modero society, it urges the need of the student's fonnation for a culture whose Ethos is printed to illuminates the moraIs in the society, where the school can educate for the respect to the other in his/her option of manifesting his/her religiosity and of discussing, in a ripe and democratic way, the pertinent subjects the several manifestations in this extent, however in a critical way. Fonnerly in the origins afilie colonization ofBrazil, RT had as characteristic the catechesis, necessarily for the conversion and religious existence gane back to the faith, addressed to the Catholic Church. In elapsing of the history of the education in Brazil, R T went by some moditications until the last ending that felt with the Law of no. 9.475, sanctioned on July 22, 1997, where it puts RT as nonnal discipline, not assisting the proselytizing fonns, however of optional and limited registration to the Fundamental Teaching. PCNs of healthy RT are divided in tive axes, with which Ethos is the main focus contemplated in this work, excelling for the fonnation of values that seek to the reflection of a human coexistence based in the respect and in the tolerance, understanding that the religious difference, in their several continuations, represents a wealth dimension that should generate a healthy atmosphere, especially the scholar, excelling for the fonnation of the citizenship and of the right manifesting his/her religious option, looking for to contribute for the construction of an Ethos that gives opening to the transcendent in the most several fonns